Step 1: The exponent in the numerator can be simplified by adding: 3 + 2 = 5. So we have 4x^5/6x.
Step 2: We can simplify the coefficient in the numerator by multiplying: 4 * 3 = 12. So we have 12x^5/6x.
Step 3: We can simplify the exponent by subtracting: 5 - 1 = 4. So we have 12x^4/6x.
Step 4: We can reduce the fraction by canceling out the common factor of 6. 12 ÷ 6 = 2 and x/x = 1. So we have 2x^4/1.
The complete answer is 2x^4.
4x^3•3x^2/6x
Step 1 - simplify the exponent in the numerator
Step 2 - Simplify the coefficient in the numerator
Step 3 - Simplify the exponent from numerator and denominator
Step 4 - Reduce and write the complete answer
1 answer